A DEIXIS ANALYSIS OF DONALD TRUMP PRESS CONFERENCE CORONAVIRUS TASK FORCE - Fajar Muhammad Fathurrohman; Lilis Suryani (PROJECT (Professional Journal of English Education), 2021)
Deixis is the study of deictic or indexical articulations in language exchanges, prefaces, and monolog like you, presently, today. Deixis can be named as a unique sort of linguistic property, managing increasingly natural syntactic classifications of individual, place, time. The purpose of this research are to describe the types and the most dominant of the deictic words used in the Donald Trump Press Conference Coronavirus Task Force. The researchers designed this research as descriptive qualitative research. The data was gathered from a speech of donald trump press conference and using theory Yule (1996). The result showed that there are three types of deixis, they are Personal Deixis, Time Deixis and Place Deixis. This research found that there are three types of deixis in press conference, they are Personal Deixis 23 occurances, Time Deixis 8 occurance, Place Deixis 1 occurance. Based on this analysis it can be concluded that personal deixis is the most dominant types of deixis used than the other types. Keywords:  Deixis, Donald Trump, Coronavirus